Nucleation sites and forest recovery under high shrub competition - Ursell, Tara; Safford, Hugh D. (Ecological applications, 2022)
Forests currently face numerous stressors, raising questions about processes of forest recovery as well as the role of humans in stimulating recovery by planting trees that might not otherwise regenerate. Theoretically, planted trees can also provide a seed source for further recruitment once the planted trees become reproductive, acting as “nucleation” sites; however, it is unclear whether changing site conditions over time (e.g., through the growth of competitors like woody shrubs) influences establishment in the long term, even if seed availability increases. We tested the nucleation concept in a system where shrub competition is known to influence tree establishment and growth, performing an observational study of sites within and close to newly reproductive planted stands in yellow-pine (YP) and mixed-conifer ecosystems in the Sierra Nevada, California. We surveyed and then modeled both seedling occurrence and density as a function of distance to seed sources, competing woody vegetation, and other environmental characteristics. We found that proximity to a planted stand was associated with an increase in the probability of YP seedlings (species more likely to originate from the planted stand) from 0.33 at 35 m from the planted stand to 0.56 directly adjacent to the stand and 0.65 within the stand. However, we found no significant effect of proximity on YP seedling density. This proximity effect suggests that seed availability continues to be a driver of recruitment several decades postwildfire, though other processes may influence the expected density of recruits. Proxies for competitive pressure (shrub volume and shrub cover) were not significant, suggesting that competing vegetation did not have a major influence on recruitment. Though seedling presence and density appeared to be independent of shrub impacts, we did find that shrubs were significantly taller than seedlings. Therefore, we suggest that shrubs may not limit seedling establishment, but they may negatively affect seedlings’ ability to grow and serve as a seed source for further recruitment and forest expansion. Altogether, we find that planting may provide a statistically significant but small role in driving recruitment outside of the planted site.